ChemInform Abstract: Pressure‐Induced Structural and Electronic Transition in Sr2ZnWO6 Double Perovskite. Issue 37 (August 2016) - Li, Nana; Manoun, Bouchaib; Tang, Lingyun; Ke, Feng; Liu, Fengliang; Dong, Haini; Lazor, Peter; Yang, Wenge
Abstract: Polycrystalline Sr2 ZnWO6 is prepared by staged calcination of stoichiometric amounts of SrCO3, ZnO, and WO3 in air (Al2 O3 crucible, 1.